Education for sustainable agriculture: a typology of the role of teaching farms in achieving learning goals and objectives. Issue 6 (3rd July 2017) - Monaghan, Kelly; Swisher, Marilyn; Koenig, Rosalie L.; Rodriguez, Juan C.
Abstract : Teaching farms have recently gained popularity, but they are often expensive venues per student credit hour. It is therefore important they are used effectively. This research explored why faculty members use teaching farms, their goals and objectives with regard to the farm, and how they integrate teaching farms into curriculum. Twenty interviews were completed with faculty representing 15 institutions. A combined inductive and deductive approach was used to analyze data. The result was a typology of the roles of teaching farms in achieving educational goals and objectives. Four types of roles emerged: enhancement, competency, exploration, and foundation. Three of the four types reflect one of three models of higher education prevalent in the US. Our research suggests a better understanding of educational theory and pedagogy, combined with a firm appreciation of the different models of higher education could significantly enhance the quality of the learning experience provided on teaching farms.